PENERAPAN MODEL PROBLEM BASED INSTRUCTION (PBI) UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DI SEKOLAH MENENGAH ATAS - Adhistia Amelia; Hartono Hartono; Diah Kartika Sari (Jurnal Penelitian Pendidikan Kimia: Kajian Hasil Penelitian Pendidikan Kimia, 2014)
The Application of Problem Based Instruction (PBI) to Improve Science Process Skills in Senior High School. This research is action research that consist of three cycles and placed in class XI IPA 2 SMAN 1 Palembang. Stages of each cycle are plan, act, observe, and reflect. Data were obtained from the observation sheet of student’s science process skills and the final test cycle. The average percentage of student’s science process skills in the first cycle of57.82%, the second cycle of 75.2%, and 86.59% for the third cycle. The results showed that the application of the Problem Based Instruction could improve students’ science process skills classXI IPA 2 SMAN 1 Palembang.